MENINGKATKAN KOMPETENSI RISET MELALUI PELATIHAN PENGOLAHAN DATA DENGAN SPSS DAN EVIEWS - Irbar, Alhapsi; M Magasing, Diyana; Muhammad, Fitriani; Adam, Adiyana; Iryanto, Muhammad (Al-Mulk: Jurnal Pengabdian Masyarakat, 2023)
Community service activity (PKM) on "Data Processing Training with SPSS and Eviews" carried out by Islamic Economics and Business Fazkultas Students of the IAIN Ternate Sharia Financial Management study program aims to introduce and train participants in this case students in Islamic studies using SPSS and Eviews software as an aid in carrying out statistical data analysis both for the purposes of courses related to data, or scientific work in the form of journals, as well as final thesis assignments. This training was attended by 30 participants from the MKS study program and was carried out in the FEBI laboratory building for one day using the 4 stages are the preparation stage, the invitation delivery stage to participants and resource persons, the activity implementation stage and the last is the evaluation stage. The results of this training activity are that the participants are quite enthusiastic and enthusiastic about participating in the training even though there are several obstacles. With training like this, participants, especially students, can increase their knowledge about using the SPSS and Eviews applications.Keywords: Student Competence; Data Processing; SPSS; Eviews.